PENGARUH APLIKASI TIKTOK TERHADAP EKSPRESI KOMUNIKASI VERBAL DAN NONVERBAL MAHASISWA FAKULTAS ILMU ADMINISTRASI UNIVERSITAS BRAWIJAYA - Farica Salsabila Putri Agustina (Jurnal Komunikasi, 2024)
In the current era, TikTok is the social media that is ranked first in terms of the most widely used by the public, especially students. TikTok began to gain attention during the pandemic, replacing Musical.ly, which is a social media created as a facility for communicating, exchanging information and distributing content between users online. The development of social media has changed the way humans communicate both in virtual networks and in person. This research aims to describe the influence of the expression of using TikTok social media in the scope of verbal and nonverbal communication on FIA UB students in 2024. The research method used is a qualitative method with interviews to make research easier. The instruments used were questions regarding FIA UB students' views on the TikTok application and the influence of TikTok on daily interpersonal communication. The results of the research show that there is a continuous expression and influence due to the use of the TikTok application on the interpersonal communication of FIA UB students